Antidepressant-like activity of oroxylin A in mice models of depression: A behavioral and neurobiological characterization - Wu, Zhong-hua; Fan, Hua; Gao, Shang-yan; Jin, Yan-fei; Cheng chen,; Jiang, Bo; Shen, Jian (Frontiers in Pharmacology, 2022)
Depression is a mood disorder which causes a huge economic burden to both families and societies. However, those monoamine-based antidepressants used in clinical practice have been found to have various limitations. Therefore, currently it is very necessary to explore novel antidepressant targets and medications. As a main active component extracted from Scutellariae radix, oroxylin A possesses many pharmacological functions such as anti-cancer, anti-inflammation and neuroprotection. Here, the present study aims to investigate whether oroxylin A possess antidepressant-like actions using the chronic unpredictable mild stress (CUMS) and chronic restraint stress (CRS) models of depression, forced swim test, tail suspension test, open field test, sucrose preference test, western blotting, immunofluorescence and viral-mediated gene interference. Our results revealed that treatment of oroxylin A fully prevented both the CUMS-induced and CRS-induced depressive-like behaviors in mice. Moreover, the protecting effects of oroxylin A against CUMS and CRS on mice behaviors were accompanied with a significant enhancement on the levels of brain-derived neurotrophic factor (BDNF), phosphorylated tyrosine kinase B (pTrkB), phosphorylated cAMP-response element binding protein (pCREB) and neurogenesis in the hippocampus. Furthermore, genetic knockdown of BDNF and TrkB in the hippocampus remarkably abolished the antidepressant-like efficacy of oroxylin A in both the CUMS and CRS models of depression, proving that the hippocampal BDNF-TrkB system participates in the antidepressant mechanism of oroxylin A. In summary, our findings are the first evidence showing that oroxylin A possesses potential of being an antidepressant candidate.